(untitled) (Razão e Fé, 2021)
This article intends to demonstrate the sacrificial character of Mass, as seen on Exodus’s chapter 12 and it’s depictment of the establishment of Easter, in which it’s seen the image of the immolated lamb who keeps death at bay and prepares the liberation of the hebrew from the house of slavery. It also analyses, with the same objective, the texts regarding the formation of the New Alliance in the Last Supper that Jesus shared with the Apostles and the narrative of the Passion, by which Our Lord, the Lamb of God who takes away the sin of the world, completed the work of redemption and freed men from the servitude of sin. Lastly, we turn our gaze towards some contemporary ecclestial magistery’s documents, where we intended to find doutrinary and dogmatic elements regarding the Mass and how the actualization of the Cross’s sacrifice takes place through the actions of the Church, Mystic Body of Christ.